RESERVOIR CHARACTERISTICS BEKASAP FORMATION SANDSTONES GIUNI FIELD IN CENTRAL SUMATRA BASIN - CHOANJI (NIM : 22013301), TIGGI
Giuni field is an oil field located in the eastern edge of Central Sumatra Basin, Riau, which produces hydrocarbons in the reservoir interval of 1440 and 1460 on Bekasap Formation. The discovery of hydrocarbons in this field was initiated in 1974 on well G-1 and followed by other wells - exploratory wells and other development. This field has been enhanced by using waterflood, and so it’s need more comprehensive reservoir model for further development strategy. The main reservoir sandstones at Giuni Field are meandering channel affected by the influence of the tides on estuarine environment. Litofasies consists of several types, including: (1) gravelly glauconitic sandstone, (2) gravelly calcareous sandstone, (3) gravelly sandstone, (4) medium - coarse glauconitic sandstone, (5) fine glauconitic calcareous sandstone, (6) very fine – fine glauconitic sandstone, (7) fine - medium glauconitic sandstones, (8) very fine – fine calcareous sandstones, (9) bioturbated mudstone. This litofacies are grouped into different facies association, which are: (1) fluvial - tidal channel facies, (2) tidal sandbar facies, (3) salt marsh facies. Based on the method of hydraulic flow units using the equations Flow Zone Indocator (FZI), association facies body of sandstones will be grouped into several types of rock types (RT), which channel facies has a rock type III and II, for tidalsandbar facies have rock type II and I, and floodplain facies have rock type I. Facies modeling, property, and the rock type with controlled wells in the end resulted a better calculation of permeability than the permeability of the formula petrophysical calculations are commonly used as compared to the core data as a validation.